Analysis of fMRI time-series by entropy measures - Mikoláš, Pavol; Vyhnánek, Jan; Škoch, Antonín; Horáček, Jiří (Neuro endocrinology letters, 2012)
Entropy is a measure of information content or complexity. Information-theoretic modeling has been successfully used in various biological data analyses including functional magnetic resonance (fMRI). Several studies have tested and evaluated entropy measures on simulated datasets and real fMRI data. The efficiency of entropy algorithms has been compared to classical methods based on the linear model. Here we explain and summarize entropy algorithms that have been used in fMRI analysis, their advantages over classical methods and their potential use in event-related and block design fMRI.
Keywords: mozek; Signal-To-Noise Ratio; Models, Neurological; Algorithms; algoritmy; poměr signál - šum; lidé; Brain; Magnetic Resonance Imaging; Entropy; Humans; modely neurologické; magnetická rezonanční tomografie; entropie